Source apportionment of size-segregated atmospheric particles and the influence of particles deposition in the human respiratory tract in rural and urban locations of north-east India. (September 2020) - Garaga, Rajyalakshmi; Gokhale, Sharad; Kota, Sri Harsha
Abstract: Aerosol samples were collected using eight stage non-viable Andersen cascade impactor at three urban and two rural sites in north-east India during 2018 covering three seasons i.e., winter, summer and monsoon. The size-segregated samples collected in the selected locations were carefully analysed in terms of deposition in human respiratory tract using inhalation and deposition curves. Seasonal variation of fractional deposition of particulate matter (PM) in human respiratory tract was observed. For example, during winter, in one of the urban sites i.e., S3 (0.61) the maximum deposition was in Pulmonary (P) region, while in the case of other sites, the maximum deposition was in Nasopharyngeal (NOPL) region. Regional deposition in P was high in S1 and S3 when compared with other sites. Vehicular emissions was dominant in both S1 and S3 in P, while biomass burning being dominant in S3 which could be the reason for maximum deposition in P. Positive matrix factorization (PMF) revealed five to eight factors at each individual site in NOPL, tracheobronchial (TB) and P regions: biomass burning (accounting for 7–32% of PM), coal combustion (14–27%), construction dust (9–25%), dust emissions (17–28%), industrial emissions (12–26%), oil refinery (18%), secondary aerosols (17–33%) and vehicular emissions (12–39%). Dominant sources in urban and rural areas were vehicular emissions and dust emissions, respectively. Therefore, the present study highlights the importance of analyzing source apportionment of PM at ultrafine scale and forms a basis upon which the future air quality studies and mitigation strategies can be formulated in this region. Graphical abstract: Image 1 Highlights: One-year size resolved PM samples were collected in five locations in Assam, India. Samples were analysed in terms of deposition in human respiratory tract. PMF revealed five to eight factors at each individual site in NOPL, TB and P regions. Dust emissions was predominant source in individual masses of PM. While size resolved PM revealed vehicular emissions being dominant in fine scale.